Exile, incorporated: the body in the Book of Ezekiel - Liebermann, Rosanne (Oxford University Press, 2024)
"The book of Ezekiel makes rhetorical use of the human body to construct an exile-centred Judean identity. This focus on the body is inextricable from Ezekiel's setting in the sixth-century BCE Judean exile to Babylonia. In such a context of upheaval, all the displaced group reliably retains are their bodies. Even so, the material surroundings of those bodies change completely, calling previously accepted ways of being into question. The book of Ezekiel reveals acute awareness of this situation, evoking bodily practices and embodied experiences that serve to construct a Judean identity based on existence outside of the land of Judah. This identity excludes both non-Judeans as well as the Judeans who remained in Judah. The book of Ezekiel seeks to achieve this exclusion via descriptions of bodily practices-including circumcision, dress, and the observance of a cultic calendar-that distinguish its constructed in-group of exiled Judeans from outsiders. Ezekiel also evokes the embodied emotion of disgust regarding the bodies of those with "outsider" practices, which in turn encourages the practice of segregation and endogamy within the in-group. Focusing on the bodies in the book of Ezekiel also highlights how the text presents hierarchies within the exilic Judean group, which itself contains bodies differentiated by gender and priestly or non-priestly descent. Reading the text in this way reveals how the book of Ezekiel constructs a model of a variegated community able to embody a Judean identity that not only survived-but was based on-life outside of the land of Judah"--